PELAYANAN DALAM PEMBUATAN E-KTP DI KANTOR CAMAT KECAMATAN SELAKAU KABUPATEN SAMBAS - Sahari E.01110063, Lukman (FISIP Universitas Tanjungpura, 2014)
The problem of service quality in handling e-ID card at the section of government at the sub-district office of Selakau is the incompatibility of the process for obtaining the e-ID card with the standard operating procedures (SOPs) as well as the vision and mission of the sub- district office of SELAKAU, lack of clarity of information about the certainty of the completion time for administrating of e –ID card, unsatisfactory service of the district office employees, the length of adjustment process when errors occur at the process of updating the data of e-ID card, the use of temporary identity certificate for the incomplete administration of e-ID card, internet network connection disruption and lack of service support facilities such as seats for citizens who employing of the creation of e-ID cards.The purpose of this study was to determine the service quality of employees in the creation of e-ID card at the section of government at the sub-district office, district of Selakau which include reliability, responsiveness, assurance, empathy, tangibles. The researcher focused on the poor service quality of employees in the administration of e-ID card at the section of government at the sub-district office, Selakau district. This study applied a descriptive research with a qualitative approach. The results showed that the employee did not provide adequate information about the time of completion for administering e-ID card, supplied unsatisfactory services to citizens, used temporary identity certificate for the incomplete administration of e-ID card. The sub-district office of Selakau as well had commotion of internet network connection and lack of service support facilities such as seats for citizens who employing the administration of e-ID card. Based on the findings of study, it is strongly suggested that the employees at the district office of Selakau can provide satisfactory information about the time of completion for administering e-ID card, supply satisfactory services to citizens who employing the administration of e-ID card and provide adequate facilities and infrastructure that support the management of e-ID services for residents such as provision of internet network and chairs for waiting. Keywords: Quality, Service, Employees, e-ID card, Information, Sub-district Office of Selakau